The Swiss flood and landslide damage database: Normalisation and trends. (3rd December 2018) - Andres, Norina; Badoux, Alexandre
Abstract : Switzerland is prone to many natural hazards causing high yearly damage to infrastructure and settlements. In this study questions about trends in data on damage from floods, debris flows and landslides are addressed and a potential connection to climate change is discussed. The data set of the Swiss flood and landslide damage database was normalised with three different approaches and trend tests were applied to yearly damage data from the period 1972–2016. Socio‐economic developments including those related to population and wealth were accounted for. The normalisation of the nominal damage data resulted in much higher values in the earlier years of the study period, especially for high damage years. Total and mean damage were both around twice as high with normalisation. Around 71–75% of the total (nominal and normalised) damage was found to occur from June through August, and spatial analysis showed the highest damage in central Switzerland and along river reaches in the main Alpine valleys. The results indicated no statistically significant increase over time in yearly nominal damage data or in data normalised with any of the three approaches. Potential effects of climate change on damage data therefore were not detected.